Multicentered study of patient outcomes after declined for early liver transplantation in severe alcohol-associated hepatitis. Issue 4 (19th April 2023) - Hsu, Christine C.; Dodge, Jennifer L.; Weinberg, Ethan; Im, Gene; Ko, Jimin; Davis, William; Rutledge, Stephanie; Dukewich, Matthew; Shoreibah, Mohamed; Aryan, Mahmoud; Vosooghi, Aidan; Lucey, Michael; et al.
Abstract : Background: Early liver transplantation for alcohol-associated hepatitis is controversial in part because patients may recover, and obviate the need for liver transplantation. Methods: In this retrospective study among 5 ACCELERATE-AH sites, we randomly sampled patients evaluated and then declined for liver transplantation for alcohol-associated hepatitis. All had Model of End-Stage Liver Disease (MELD) >20 and <6 months of abstinence. Recompensation was defined as MELD <15 without variceal bleeding, ascites, or overt HE requiring treatment. Multilevel mixed effects linear regression was used to calculate probabilities of recompensation; multivariable Cox regression was used for mortality analyses. Results: Among 145 patients [61% men; median abstinence time and MELD-Na was 33 days (interquartile range: 13–70) and 31 (interquartile range: 26–36), respectively], 56% were declined for psychosocial reasons. Probability of 30-day, 90-day, 6-month, and 1-year survival were 76% (95% CI, 68%–82%), 59% (95% CI, 50%–66%), 49% (95% CI, 40%–57%), and 46% (95% CI, 37%–55%), respectively. Probability of 1-year recompensation was low at 10.0% (95% CI, 4.5%–15.4%). Among patients declined because of clinical improvement, 1-year probability of recompensation was 28.0% (95% CI, 5.7%–50.3%). Among survivors, median MELD-Na at 30 days, 90 days, and 1-year were 29 (interquartile range: 22–38), 19 (interquartile range : 14–29), and 11 (interquartile range : 7–17). Increased MELD-Na (adjusted HR: 1.13, p <0.001) and age (adjusted HR: 1.03, p <0.001) were associated with early (≤90 d) death, and only history of failed alcohol rehabilitation (adjusted HR: 1.76, p =0.02) was associated with late death. Conclusions: Liver recompensation is infrequent among severe alcohol-associated hepatitis patients declined for liver transplantation. Higher MELD-Na and age were associated with short-term mortality, whereas only history of failed alcohol rehabilitation was associated with long-term mortality. The distinction between survival and liver recompensation merits further attention. Abstract :